Monetary Whispers Across Space - Azis, Iwan J.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2026)
This open access book explores how macroeconomic policy, specifically monetary policy, interacts with interregional inequality. Using the case of monetary policy in Indonesia, a country with high interregional inequality, it examines how national-level policies can inadvertently deepen disparities between regions, and in turn contribute to the limited effectiveness of the policies. Undermining the local conditions, institutions, and spatial dynamics that could strengthen the centripetal forces plays a key role in such a negative feedback loop. Although monetary policy is designed to be neutral, the book argues that it can have uneven regional impacts. By amplifying the divide between already developed areas and those still catching up, such policies may undermine theiown effectiveness. This self-reinforcing cycle is significantly shaped by the behavior of local banks' liquidity preferences, risk perceptions, and lending strategies, which can either connect or disconnect national policy goals from inclusive regional development. Drawing on macroregional data, quantitative models, field surveys, and interviews with local officials and bankers, the book offers compelling insights into one of the central challenges of economic policymaking in a diverse and decentralized nation. It also presents a powerful critique of the (3z(Bspatial blindness(3y (Boften embedded in economic governance.s
Chapter 1: Introduction -- Chapter 2: Space and Money -- Chapter 3: Expanding Unequally and Unproductively -- Chapter 4: Ignoring Spatial Factors -- Chapter 5: Broken Ladder: Was Monetary Policy Effective? -- Chapter 6: Go Behind the Wall -- Chapter 7: Reflections.
Accessibility summary: This PDF has been created in accordance with the PDF/UA-1 standard to enhance accessibility, including screen reader support, described non-text content (images, graphs), bookmarks for easy navigation, keyboard-friendly links and forms and searchable, selectable text. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com. Please note that a more accessible version of this eBook is available as ePub.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Macroeconomics; Economic policy; Political planning; Urban economics; Finance, Public; Macroeconomics and Monetary Economics; Economic Policy; Public Policy; Urban Economics; Public Finance